The Development of a Leadership Competency Model for Administrative Staff at a Public University in Foshan City, Guangdong Province, China - Han, Huimin; Mhunpiew, Nathara (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
Effective leadership among administrative staff is essential in the internationalization of higher education. This study employed a mixed-method design to develop a leadership competency model for administrative staff at a public university in Foshan City, Guangdong Province. The ideal leadership competencies for university administrative staff were identified through a systematic review, categorized into five categories: motives, traits, self-concept, knowledge, and skills. This study concluded that skills and knowledge were weaknesses of leadership competencies and need priority development. Furthermore, within each category specific leadership competencies require prioritization. All five leadership competencies were incorporated into the leadership competency model, highlighting the elements that require priority development. This study provides theoretical support for leadership training and development among administrative staff at a public university in Foshan City.